Dendritic WS₂ nanocrystal-coated monolayer WS₂ nanosheet heterostructures for phototransistors - Zhan, Li (2022)
Two-dimensional tungsten disulfide (WS2), as one of the widely concerned members of the transition metal dichalcogenides family, has been studied broadly by its outstanding photonic and electronic properties. Since all of the research works focus on size and the number of layers, the dendritic structure WS2 has been scarcely reported. In our study, we make use of atmospheric pressure chemical vapor deposition (APCVD) to control the synthesis of dendritic WS2/monolayer WS2 heterostructures on the SiO2/Si substrate. The stacking morphology of the heterostructure is verified by AFM, Raman, and PL spectra. The effects of growth times and carrier gas flux on the quasi-epitaxial growth of WS2 films with dendritic structures have been systematically studied. In addition, the transition between fractal, dendritic, and compact morphologies with the increase of the growth times (carrier gas flux) are more significant. The compact morphology and difference of contact potential between the adjacent dendritic structures are characterized by Kelvin probe force microscopy (KPFM). Moreover, the as-fabricated FET devices exhibit excellent electronic properties (on/off ratio, carrier mobility, photoresponsivity, and response time are about 106, 11.42 cm2 V-1S1-, 46.6 mA/W, and 105.5 μs, respectively). This study paves the way for the rational design of high-sensitivity fractal-enhanced phototransistor devices for industrial and commercial applications.